A study on the influence of green advertising design and environmental emotion on advertising effect - Kao, Tsai-Feng; Du, Yi- Zhan (Journal of cleaner production, 2020)
In the discussion on advertising effect, the self-reference effect and argument quality are regarded as the factors affecting consumption judgment. This research aims to discuss the advertising effect of advertising design and the environment-protecting emotion of graphic configuration of self-reference and argument quality, as well as their effect on advertising effect. With the use of the quasi-experimental research method, this research adopts the Between Subject Factorial Design of advertising design (with self-reference and strong arguments, with self-reference and weak arguments, with no self-reference and strong arguments, and with no self-reference and weak arguments), and environment-protecting emotion (positive and negative) is adopted, with a total of 4 experimental situations, in order to manipulate the variables and measure the advertising effect. The results find that the advertising design with self-reference and strong argument has the best advertising effect; positive moral emotion and social emotion have better advertising effect; and under the action of emotion, the subjects’ preference for advertising design will also change. This research is helpful to establish and optimize the green advertising design to understand the relationship between factors affecting the advertising effect and the benefits of green marketing.